1996
DOI: 10.1002/(sici)1099-0518(199602)34:3<387::aid-pola7>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structure, reactivity, and thermal properties of new cyclic phosphine oxide epoxy resins cured by diamines

Abstract: A new type of epoxy resin which contained cyclic phosphine oxide group in the main chain was synthesized. The structure of the new type of epoxy resin was confirmed by elemental analyses (EA), infrared spectroscopy (IR), and 1H‐NMR and 13C‐NMR spectroscopies. In addition, compositions of the new synthesized cyclic phosphine oxide epoxy resin (EPCAO) with three curing agents, e.g., bis(3‐aminophenyl)methylphosphine oxide (BAMP), 4,4′‐diamino‐diphenylmethane (DDM), and 4,4′‐diaminodiphenylsulfone (DDS), were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…An epoxy resin containing a cyclic phosphine oxide group in the main chain (Scheme )133 and a tetrafunctional epoxy containing phosphorus oxide and nitrogen groups in the main chain (Scheme )134 were synthesized and cured with bis(3‐aminophenyl)methylphosphine oxide (BAMP), 4,4′‐diaminodiphenylmethane (DDM) or 4,4′‐di‐aminodiphenyl sulfone (DDS), and compared with commercial resins. In any combination, either cured with phosphorus‐containing BAMP, DDM or DDS, the phosphorus‐containing epoxy resins showed higher char yields than bisphenol A or novolac‐type commercial resins.…”
Section: Flame‐retardant Epoxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An epoxy resin containing a cyclic phosphine oxide group in the main chain (Scheme )133 and a tetrafunctional epoxy containing phosphorus oxide and nitrogen groups in the main chain (Scheme )134 were synthesized and cured with bis(3‐aminophenyl)methylphosphine oxide (BAMP), 4,4′‐diaminodiphenylmethane (DDM) or 4,4′‐di‐aminodiphenyl sulfone (DDS), and compared with commercial resins. In any combination, either cured with phosphorus‐containing BAMP, DDM or DDS, the phosphorus‐containing epoxy resins showed higher char yields than bisphenol A or novolac‐type commercial resins.…”
Section: Flame‐retardant Epoxiesmentioning
confidence: 99%
“…A few studies have been reported in the literature concerning curing of epoxy resins with bis(aminophenyl)methylphosphine oxide (Scheme ), as well as the thermal and combustion performance of the resins containing this oxide 56, 87, 133, 149–153. Von Gentzkow et al 129 have used the analogous bis(aminophenyl)ethylphosphine oxide (Scheme ) to cure a phosphorus‐containing epoxy resin.…”
Section: Flame‐retardant Epoxiesmentioning
confidence: 99%
“…The cured epoxy resins are of high crosslinked network that often exhibit high tensile strength and modulus [1], excellent chemical and corrosion resistance [2], and good thermal stability [3]. However, the ordinary epoxy resin cannot crosslink alone without curing agents or accelerant.…”
Section: Introductionmentioning
confidence: 99%
“…The cured epoxy resins are of high crosslinked network that often exhibit high tensile strength and modulus [1], excellent chemical and corrosion resistance [2], and good thermal stability [3]. However, the ordinary epoxy resin cannot crosslink alone without curing agents or accelerant.…”
Section: Introductionmentioning
confidence: 99%